The life and works of Geronima T. Pecson - Tarlit, Rodolfo Y.; Faderon, Rosalie B.; Santos, Herminia H. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1985)
This is a historical and bibliographical study which presents a narrative record of the life history and works of Geronima T. Pecson from the time of her birth to the present. It identifies, describes and evaluates her achievements and contributions to education, social work, health, community and rural improvements, politics and international affairs; and compiles a bibliography of her various works - books, articles, book reviews, speeches, messages, statements, interviews and reports - both published and unpublished from 1929 to 1980.
The bibliography is annotated and arranged chronologically. Undated works are placed at the end of the bibliography and arranged alphabetically by title. Appended are: 1) a bibliography of sources or writings about Mrs. Pecson which is arranged alphabetically by author or title, if there is no author; and 2) a "Preliminary Inventory of the Geronima T. Pecson Papers and memorabilia" prepared by the University Archives and Records Depository, U. P. Main Library. Also provided is a subject index to the works of Mrs. Pecson where reference is made to the entry number.
Mimeographed.
Special Problem (Master of Library Science)
Keywords: Pecson, Geronima Tomeldan